Optimalisasi Gulma Senduduk (Melastoma malabathricum L.) di sekitar tanaman Aren (Arenga pinnata) sebagai Pestisida Nabati pada Tanaman Cabai (Capsicum frutescens L.) - Diadara, Dhiva Kinanti; Herlin, Weri; Mulya, Firman; Ramadani, Salwa Novia; Hasibuan, Thresia Firmaida; Ardianto, Febri; Pardede, M. Rabiul (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2024)
Diadara, D. K., Herlin, W., Mulya, F., Ramadani, S. N., Hasibuan, T. F., Ardianto. F., & Pardede, M. R. (2024). Optimization of senduduk weed (Melastoma malabathricum L.) around aren (Arenga pinnata) plants as vegetable pesticide on chili plants (Capsicum frutescens L.). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang 21 Oktober 2024. (pp. 186–194). Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Cayenne pepper plants (Capsicum frutescens L.) were horticultural commodity plants that have high economic value in Indonesia which were never free from the problem of pests and diseases in cayenne pepper plants. The purpose of this research was to optimize weeds that grow around sugar palm (Arenga pinnata) plants. The method of using senduduk weed (Melastoma malabathricum L.) as a vegetable pesticide on chili plants (Capsicum frutescens L.) because was is aleolkimia content that has potential as a natural ingredient to control pests. This study tested senduduk extracts on chili plants to determine how effective they were in controlling pest attacks. The results showed that the use of senduduk weed extracts had a significant effect in reducing pest populations and increasing the productivity of chili plants. The conclusion that Optimizing senduduk weed around palm plants as a vegetable pesticide can be an environmentally friendly alternative to organic farming while helping to manage weeds that are often considered harmful.